Faktor resiko kejadian peningkatan kadar transminase pada penggunaan obat antituberkulosis pasien tuberkulosis paru di RST Wijayakusuma Purwokerto - Alya Andina Dasuki; Annisa Farida Muti; Hany Yusmaini (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Most of the tuberculosis cases reported in Indonesia were in provinces with high population density, including Central Java. The combination of first-line antituberculosis drugs including pyrazinamide, isoniazide and rifampicin has the potential to cause hepatotoxicity as indicated by an increase in transaminase levels. Incidence of elevated transaminase levels leading to drug resistance and treatment failure. Early detection of elevated transaminase levels by antituberculosis drugs is important by studying predisposing risk factors. The purpose of this study was to determine the relationship between risk factors and the incidence of increased levels of transaminases due to the use of anti-tuberculosis drugs in patients with pulmonary tuberculosis at RST Wijayakusuma Purwokerto. This type of research is an observational analytic study with a cross-sectional design. A total of 80 samples were selected by random sampling. Data collection is done by viewing and recording the patient's medical record. Data were analyzed using the Chi-squared test and Logistic Regression test. The results of the bivariate analysis with the Chi-Square test showed that there was a significant relationship between old age (p = 0,000), female gender (p = 0.035), malnutrition (0,000), length of treatment (p = 0.026) and a history of taking other drugs. (p = 0.008). The most influential factor was the elderly (OR = 8.815) on the incidence of elevated transaminase levels; followed by nutrition status (OR=6,478).